A Bibliometric Review of the Relationship between Sustainability Accounting and Financial Risk - Judijanto, Loso; Hartoyo, Abdulrival; Chairunnas, Arnadi (Westscience Press, 2024)
This study conducts a comprehensive bibliometric analysis of the field of sustainability accounting and financial risk management, examining thematic clusters, research trends, research opportunities, and author collaborations from 1990 to 2024. Through an extensive review of literature and citation data, key thematic areas such as integrated reporting, environmental risk, and the financial impact of ESG factors were identified. Temporal trend analysis revealed an increasing focus on transparency in sustainability disclosures and the integration of corporate social responsibility into corporate risk management. Opportunities for further research were highlighted in underexplored areas including green accounting and the incorporation of non-financial risks into financial sustainability frameworks. Additionally, an examination of author networks provided insight into the collaborative dynamics among leading scholars, identifying core research groups and potential areas for new interdisciplinary studies. This study provides a structured overview of the scholarly landscape, identifying pivotal trends and gaps, thereby setting a foundation for future academic inquiries and practical applications in sustainability and financial risk management.